The concept of anxiety in practice exam among vocational school students - Tyesa Sri Handayuni; Ifdil Ifdil (Indonesian Institute for Counseling, Education and Theraphy, 2020)
Each student experiences an educational process so that can become a quality human being in accordance with the objectives of level education are more required to carry out work practices in accordance with their majors. Things that are done when the practice sometimes causes uncomfortable feelings, one of which is feeling anxious. Anxiety can be interpreted as a situation where someone feels afraid, feels depressed, feels worried about things that will happen, so that can interfere with the learning process. In this article will explain the concept of anxiety and aspects that affect anxiety that can be experience by students in general in vocational high schools.